208k views
5 votes
3xy^3 + 5- x- 2xy^3= xy^3 +11

Solve please

User Yaffa
by
5.4k points

2 Answers

4 votes
Hope you can read this. I didnt wanna make a blocky chunk of text with all the exponents so I handwrote it :)
3xy^3 + 5- x- 2xy^3= xy^3 +11 Solve please-example-1
User Sandip Patel
by
5.6k points
2 votes

Answer:


Step-by-step explanation: 3XY 3+5-X-2XY3=XY3+11 USE THE COMMUTATIVE PROPERTY TO REODER THE TERMS...3Y3+5-X-2XY3=XY3+11 COLLECT LIKE TERMS Y3+5-X-Y3X+11..Cancel equal terms on both sides of the equation 5-x=11 move constant to the right side and change its sign -x=11-5 subtract the numbers -x=6 final answer is X=-6


User Abudayah
by
5.7k points